The moral writings of John Dewey - edited by James Gouinlock (New York Prometheus Books, 2002)
John Dewey (1859-1952), renowned educator and philosopher, has been called the national philosopher of American civilization. James Gouinlock's superb collection of Dewey's writings presents the many aspects of Dewey's ethical thought. With this collection, students and scholars alike will more readily acknowledge Dewey's substantial contribution to our understanding of the moral life.
Includes bibliographical references and index.
Keywords: Ethics